Hydrogen powered lawnmower - Mohd Rafi’uddin, Ramlan (2013)
The study and analysis of a hydrogen powered lawnmower are described. Most of the commercial lawnmower is originally powered by gasoline carbureted 2-stroke engine. The carbureted 2-stroke engines are characterized by high levels of hydrocarbon, carbon monoxide, and particulate matter emissions. Despite its poor emissions, carbureted 2- stroke engines remain a popular power source for small appliances like lawnmower because of its low cost and high power to weight ratio. The presence of hydrogen as the fuel for the internal combustion engine can improve the quality of emissions as well as the fuel consumption. The commercial model that was originally running on gasoline is adapted to hydrogen by making adjustments to the fuel delivery system. The fuel delivery system modified to use hydrogen as the sole fuel in the internal combustion engine. The original carburetor system is replaced with the fuel injection system. Redesigning the fuel delivery system can be effective in reducing or eliminating irregular combustion due to premature ignition and backfires. The hydrogen needed for the engine is generated from electrolysis in a hydrogen generator which turns water as an electrolyte into HHO or hydrogen. The measure for engine design or conversion also discussed